Afrika Zamani: n°18 & 19, 2010-2011 - Full Issue - Journal System, (Afrika Zamani, 2021)
Contents Métissage in Nineteenth Century Senegal: Hybrid Identity and French Colonialism in a West African Town Hilary Jones ..................................................... 1 Musical Hybridity in Flux: Representing Race, Colonial Policy, and Modernity in French North Africa, 1860s-1930s . Jann Pasler ........................ 21 Le cinéma, un véhicule culturel en contexte colonial Odile Goerg ..........................69 A la recherche d’un primitivisme fédérateur: le peintre Atlan et le groupe Cobra ...................................................................... 95 Anissa Bouayed ...................................................................... 95 Colonial Encounters: A Danish Planter in German East Africa ......................................................................................... 107 Marianne Rostgaard ......................................................................................... 107 Education et identité des « Portugais » en Casamance XIXè- début XXè Histoire d’une « assimilation » manquée ? Céline Labrune-Badiane ...................... 131 Camwood (PterocarpusTinctorius) in the Political Economy of the Cross and Manyu Rivers Basin of Cameroon and Some Hinterland Communities, 1916-1961 Henry Kam Kah ....................................... 149 Colonial Economic Disempowerment and the Responses of the Hlengwe Peasantry of the South East Lowveld of Zimbabwe: 1890-1965 Taderera Hebert Chisi .................................................................. 165